Institutional Transformation of Local Innovation Systems in Farmer Community of Belu, Nusa Tenggara Timur - Febri Wijayanti; Savitri Dyah; Rachmini Saparita; Akmadi Abbas (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
Institutional is one factor that must be considered in the process of technology transfer. The Local Innovation System (in this case SIDa-Belu) was trying to look at those problems in agriculture to empowering poor farmers in the area. This paper analyzed transformation intitution, which occurs during and after the proccess of SIDa-Belu Implementation. The methods used in this research is descriptive analysis with structure, conduct, performance (SCP) approach.Institutional change is a transformation proccess that is part of development. Therefore, the main objective of any institutional change is to internalize the potential for greater productivity which comes from improved resource utilization, and creating a new balance simultaneously. On SIDa-Belu implementation, institutional change encourage the change for farming groups. Before SIDa-Belu they did subsistent farming, and after implementation they make a new adjustment by external factors (permanent feedback proccess) into modern farming groups with market oriented.